(3LhGgQ GdcdGe TQM TQGFY GdESdGes - (3GdfLaj, eMeO GdfLaj, eMeO MSf Hf HGbQ, J (B1266(3g` (B1850(3es ((3eMeO Hf Ydj GdMhjRjs)
(3ChdgG (B:s
(3ChdgG(B: (3cJGH GdRcGI, GdJj gj dZI GdWgGQI hefg bJdJ fakSG RcjI, bO CadM ef RcGgG, eG Rci efce ef CMO(B... (3hYf GdTgjO(B: (3CfgG JWdb Ydi GdYed GdUGdMs
(3BNQgG (B:s
(3BNQgG(B: (3GYWge Ydi GdgLQI aj GdOjf hGdabg hGdYbd hGdebUhO ef Pdc HjGf Cf gPg hfMhgG eQLMGJ heY GdJYGQV jfHZj edGMXI GdejRGf ceG GTQfG Edi fMh Pdcs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf, L (B3: 214s
(3GdPQjYI, L (B5: 196s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis